Quality Management of Islamic Boarding Schools in Improving The Quality Of Educators - El-Yunusi, Melikai Jihan; Maimun, Agus; Kawakib, Akhmad Nurul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to examine how an Islamic boarding school implements the principles of quality management to improve the quality of educators, so that the quality of graduates of Islamic boarding schools has increased and also has high competitiveness from other educational institutions in general. Educators are the spearhead of success in the educational process. Islamic boarding schools in Indonesia have experienced a bad stigma regarding Islamic boarding school management, and this still occurs to date. Since Islamic boarding schools are poorly run, there has not been much change in the status quo in non-formal education, which is characterized as conventional, conservative, and outdated. Nevertheless, the public still strongly desires Islamic boarding schools, which are rumored to exist occasionally. Library research methods are used in this investigation. The research data source includes library resources, books, and chosen research articles pertinent to this study. According to the research findings, Kyai's responsibilities as a top leader are multifaceted; he must enhance his quality as a manager, teacher, and preacher. They can work professionally by their roles and duties and are quality in the truest sense. Providing decent salaries and ensuring teacher welfare can be a consideration for improving teacher quality to improve the quality of education; moreover, in implementing Islamic boarding schools, quality management is based on management principles, including Planning, Organizing, acting, and Controlling, which are based on quality. The implications of the results of this study for the leaders of Islamic boarding schools are that it is very important to implement quality principles, namely continuous improvement, quality standards (quality assurance), development of quality culture (development of culture), organizational changes that follow changes in vision and mission that are oriented towards quality (upside down organization) and maintaining good relationships with customers (keeping close to the customer). So that leaders can manage professionally to meet the needs of the professionalism of the Ustaz that Islamic boarding schools need.